THE CORRELATION BETWEEN HEALTHY HOUSES AND ACCESS TO SAFE DRINKING WATER WITH THE INCIDENCE OF DIARRHEA IN EAST JAVA IN 2016 - Siti Fera Irawati; Arief Wibowo (Universitas Airlangga, 2021)
ABSTRACTDiarrhea is a common endemic disease in Indonesia. In developing countries, the high prevalence of diarrhea can be attributed to the lack of clean water and proper sanitation. This study determined a correlation between access to safe drinking water and healthy houses with the incidence of diarrhea in East Java in 2016. The study applied a correlation study design. The population consisted of all diarrhea patients treated in East Java in 2016; thus, the population was used also as a sample. The data were obtained from secondary data, namely the 2016 East Java Provincial Health Profile. Pearson correlation test was used in analyzing the data. There was a correlation between healthy homes (p = 0.000) and sustainable access to safe drinking water (p = 0.000) with the incidence of diarrhea. Pearson correlation coefficient for the healthy house variable was 0.798, while the Pearson correlation coefficient for sustainable access to safe drinking water was 0.722. It can be concluded that the relationship between healthy homes and access to safe drinking water with the incidence of diarrhea in the Province of East Java in 2016 was strong enough.Keywords: diarrhea, healthy houses, access to safe drinking water.